IbM KARANG TARUNA DAN PKK DESA KOHOD PAKUHAJI MELALUI PENINGKATAN NILAI TAMBAH DALAM PENGOLAHAN LIMBAH KELAPA SEBAGAI UPAYA PENINGKATAN PENDAPATAN MASYARAKAT - Bethriza Hanum, Yudhi Chandra Dwiaji, Nurato & (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2017)
The main objective of the community service activity is to provide the partners skills on coconut waste processing technology to transform coconut waste into products with economic value. Through this transfer of technology activity, it is expected that new entrepreneurs will emerge. In addition, it is hoped that the targeted partners will be able to transfer their newly-gained skills to the neighboring communities, particularly to the Family Welfare Program (PKK) members and coconut farmer groups in Kohod village, Pakuhaji sub-district. The approaches utilized to solve the existing problems are transfer of technology method (science and technology) and entrepreneurship to generate value-added products. The activities of the Community Service Program are divided into three stages: preparation, implementation, and monitoring. The outputs of this activity are nata de coco, briquettes, and liquid smoke. All participants could follow the activities well. They were very inquisitive about the materials shown by the presenters. Follow-up activities were conducted after the participants partially implemented the knowledge presented by the Community Service Team. The purpose of the follow-up activities is to study the impact of this community service activity. As a follow-up, the participants were required to demonstrate the production process of nata de coco, liquid smoke, and briquettes from coconut shells. It is to ensure that the participants understand each stage in the waste processing of the products. Through the evaluation, it is found that in relation to coconut processing, the participants have shown improvement in their knowledge and skills. They have also realized that there are opportunities to increase their income. Around 85% of the participants responded positively to the knowledge and skills instilled by the Community Service Team.Keywords : nata de coco, liquid smoke, briquettes, coconut shells